Model Pluralisme Agama Berbasis Kearifan Lokal “Desa Pancasila” di Lamongan - Azizah, Imroatul; Kholis, Nur; Huda, Nurul (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2020)
This article aims to reveal the role of local wisdom in realizing religious tolerance in Balun, Lamongan. Interviews were conducted with village leaders, leaders and youths of three religions and community representatives, totaling 10 informants selected purposively. All interviews were recorded and then transcripts of the interview results were afforded. Data analysis employed four stages: transcription, inventory, classification, and description. This study found that the Balun community succeeded in maintaining and strengthening religious tolerance. This strength is based on several local wisdoms, for example nyadran and prayer to the deceased, which are carried out together regardless of people religious background. This inclusive activity strengthens a sense of solidarity, cohesiveness and tolerance at Balun. Local wisdom in Balun is portrayed as an interfaith meeting, conflict resolution, and fostering communal solidarity. This research contributes to the scarcity of studies that reveal the role of local wisdom in society. Similar research worth doing in order to unravel other forms of local wisdom.